Slightly more women in Germany's corporate boardrooms: Especially in DAX 30 companies - Elke Holst; Julia Schimeta (DIW Economic Bulletin, 2013)
Despite the commitment that has been expressed by German companies to bringing more women into top management, at the end of 2012, only four percent of all seats on the executive boards and just under 13 percent on the supervisory boards of the top 200 companies in Germany were occupied by women. This corresponds to an increase of one percentage point on the previous year in both cases. Nevertheless, at the end of 2012, women held almost eight percent of seats on the executive boards of the DAX 30 (up 4.1 percentage points on the previous year) and over 19 percent of seats on DAX 30 supervisory boards (up 3.7 percentage points) - which may well be attributable at least in part to the public attention focused on these companies. In companies with government-owned shares, which are often smaller than the DAX 30 or the top 200 companies, the representation of women was somewhat higher at over 11 percent on executive boards and almost 20 percent on supervisory boards. Overall, employee representatives still make up the majority of women on supervisory boards. In none of the company groups studied had the strong predominance of men declined significantly. At the start of the period under investigation. the number of women on the boards was too low and the impetus for change was too weak. Within Europe, Germany is ranked sixth in terms of the percentage of women in the top-level decision-making bodies of listed companies. On the one hand, this is indicative of even more severe difficulties faced by women seeking executive positions in other countries . On the other hand, it should be noted that German firms rank relatively high because only the supervisory boards of the DAX 30 are taken into account in the European comparison. This focus on supervisory boards of DAX companies is too narrow, however, for an accurate assessment of women's opportunities in corporate boardrooms.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; board diversity; women CEOs; gender equality; management; listed companies; private companies; public companies; quotas for women